Television Coverage and Outcome Uncertainty in Sports: Empirical Evidence from the NBA and WNBA. [Cobertura televisiva e incertidumbre en los resultados deportivos: Evidencia empírica en la NBA y la WNBA]. - Yubo Wag; Wright Hilsman; Steven Caudill; Franklin Mixon (Ramón Cantó Alcaraz, 2014)
In an important paper, Price, Remer, & Stone (2012) introduce one manifestation of referee bias called "close" bias - the idea being that because close games are more valuable, referees might officiate to keep games close. Using 990 observations from the 2011-12 National Basketball Association (NBA) season and 442 observations from the 2010 and 2011 Women's National Basketball Association (WNBA) seasons, we test conceptual models of the impact of television coverage on close bias. Our empirical results that the absolute score differential is about two points less for nationally televised NBA games and about three points less for nationally televised WNBA games, even after accounting for differences in team strength. Our results confirm and extend the earlier findings of Price, Remer, & Stone (2012). Resumen En un importante artículo, Price, Remer y Stone (2012) introducen una manifestación del sesgo arbitral llamada sesgo de "proximidad", el cual se refiere a que, dado que los partidos con marcadores ajustados son más valiosos, los árbitros podrían actuar intencionadamente para mantenerlos así. En nuestro estudio, y tras el análisis de 990 partidos de baloncesto de la temporada 2011-12 en la NBA, y de 442 partidos de las temporadas 2010 y 2011 en la WNBA, testamos varios modelos conceptuales sobre el impacto de la cobertura televisiva sobre el sesgo de proximidad. Los resultados indican que la diferencia absoluta en el marcador entre los equipos es alrededor de dos puntos menor para los partidos televisados a nivel nacional en la NBA, y sobre tres puntos menor para la WNBA, considerando las diferencias de potencial entre los equipos. De este modo, nuestros resultados confirman y extienden los hallazgos de Price, Remer y Stone (2012).